2019
DOI: 10.1016/j.healun.2019.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Increasing heart transplant donor pool by liberalization of size matching

Abstract: BACKGROUND-The heart transplant (HT) guidelines recommendation to match recipient and donors within 30% of body weight lacks a strong evidence base and is not well established in patients bridged to transplant with left ventricular assist devices (LVAD). In light of the scarcity of donor hearts, we investigated the effect of size mismatch on hemodynamics, one-year survival and length of stay (LOS) following HT. METHODS-Single-center retrospective analysis of consecutive HT patients from April 2007 to September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…On the other hand, 32% of the donor hearts that were declined due to concerns of undersizing in the UNOS database of the years 2007 to 2016 were found eligible when using the heart mass as a parameter for matching metrics. While these results promise to improve the allocation of female donor hearts, a smaller study of 288 HTx recipients showed that undersizing of the donor heart affects early hemodynamics but was without impact on one-year survival [86]. Altogether, these results suggest that efforts to improve matching metrics have the potential to increase the allocation of donor organs judged not suitable based on current recommendations.…”
Section: Heart Transplantationmentioning
confidence: 90%
“…On the other hand, 32% of the donor hearts that were declined due to concerns of undersizing in the UNOS database of the years 2007 to 2016 were found eligible when using the heart mass as a parameter for matching metrics. While these results promise to improve the allocation of female donor hearts, a smaller study of 288 HTx recipients showed that undersizing of the donor heart affects early hemodynamics but was without impact on one-year survival [86]. Altogether, these results suggest that efforts to improve matching metrics have the potential to increase the allocation of donor organs judged not suitable based on current recommendations.…”
Section: Heart Transplantationmentioning
confidence: 90%
“…1,2,6,11,12 This type of targeted size matching allows avoidance of complications related to oversizing, such as bronchial compression, delayed chest closure, and prolonged length of stay. 13,14 F I G U R E 1 The TCV segmentation is shown in the axial plane (A), coronal plane (B), and 3-dimensional reconstruction (C). TCV mass is in Red and HMIII is in green…”
Section: Discussionmentioning
confidence: 99%
“…Lacking a heart size measure like PHM in children, TCV‐based size matching has recently emerged as a method for more precise organ matching and has demonstrated on numerous occasions the potential to expand the donor pool for listed patients 1,2,6,11,12 . This type of targeted size matching allows avoidance of complications related to oversizing, such as bronchial compression, delayed chest closure, and prolonged length of stay 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…Current indications in adult heart transplantation consider an ideal DRWR to be between 0.8 and 1.2, but there are several studies on the impact of greater size mismatch, and it seems that is not associated with a higher mortality. [11][12][13] In the pediatric transplant population, these constraints have always been handled less rigidly as organ size discrepancies between children may have less impact than in adults and waiting times for ideal matches could be excessive due to limited pediatric donor availability. The consequences of enlarging the matching criteria have been largely debated, mostly about early and late complications.…”
Section: Discussionmentioning
confidence: 99%